EDUKASI MENSTRUASI PADA REMAJA PUTRA DAN PUTRI DI PONDOK PESANTREN DARUL ULUM AL-FAUZANI PASURUAN - Budi Imtiaz, Zitni Chelsea (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2025)
Adolescence according to WHO is those who enter the transition stage between childhood and adulthood. According to the Indonesian Minister of Health, the age limit of adolescence is 10 to 19 years old and unmarried. Adolescence or puberty is a stage of development in the growth period of maturity and fertility in the reproductive organs. A sign of a woman entering puberty is the onset of menstruation. Menstruation is a natural process experienced by every woman, namely the occurrence of a bleeding process caused by the decay of the uterine wall due to the absence of fertilization. The purpose of this activity is to increase understanding and invite young men and women of Darul Ulum Al-Fauzani Islamic Boarding School to think rationally about menstrual facts and myths, handling menstrual pain, and the role of men in it. The method of this activity is health promotion by using PPT and posters as educational media and conducted by counseling to 150 adolescent boys and girls of Darul Ulum Al-Fauzani Pasuruan Islamic Boarding School. Evaluation of this activity was carried out using pre-test and post-test questionnaires. The point score knowledge of young men and women before counseling was dominantly lacking around 6.94% and after counseling the participants' knowledge increased to a good dominant around 100%. The results of the activity were obtained by increasing knowledge about menstrual myths and facts, handling menstrual pain, and the role of men in it.